An introduction to Christian mysticism : recovering the wildness of spiritual life - Baxter, Jason M., 1981- (Grand Rapids: Baker academic, 2021)
"This brief, accessibly written volume introduces key figures, texts, and themes of the mystical tradition, showing that the mystics have much to say to contemporary Christians searching for authentic modes of spirituality"--
The Christian of the Future in the Desert of Modernity: The Twentieth-Century Rediscovery of Ancient Mysticism -- Pagans Grope toward God: Piety and Prayer in Antiquity -- The Inward Turn: What Augustine Learned from the Pagans -- The Darkness of God: Dionysius the Areopagite, Gregory of Nyssa, and Meister Eckhart -- Praying with the Whole World: Natural Contemplation and the Legacy of the Desert Fathers -- How to Perform Scripture: Lectio Divina and the Renewal of the Heart -- Conclusion: The Wildness of the Spiritual Life.
Includes bibliographical references (pages 173-189) and index.
Keywords: Mysticism